MODEL PEMBINAAN MORALITAS MASYARAKAT BERBASIS EKONOMI KERAKYATAN DAN KEARIFAN LOKAL (STUDI KASUS DI PESANTREN RAKYAT AL-AMIEN SUMBERPUCUNG KABUPATEN MALANG) - Faishol, Muhammad (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2018)
Moral goodness is tailored to size-size of the Act received by the public, including the unity of certain environmental or social. Inside there are moral deed, speech or behaviour of a person in the exercise of his interaction with humans. If the person does it in accordance with the prevailing sense of values in society and an acceptable environment, then that person can be said to have good moral values, as well as vice versa. However, until recently it turned out that there are still many problems related to morality in society. When in fact moral are one of important indicators to reach communities that madani. Therefore, the need for the construction of the model of society, which in this case was conducted by the people's boarding school Al Amien Sumberpucung Malang through populist economic approach and local wisdom. This study used a qualitative approach. This research uses a three-part grand method i.e. library research is scientific papers based on the literature and books, field research, i.e. research which is based on field research, and bibliographic research, i.e. research that focuses on the idea of community-based models of morality construction of the people's economy and local wisdom with a focus of research at Pesantren People Al Amien Sumberpucung Malang. The role of the people's Islamic boarding school Al Amien Sumberpucung Malang not only have religious functions, but also have social functions. By using this strategy, the pesantren silaturrahmi capable of fostering morality society with 5 models, namely: Jagong Maton, barns, Silver piggy bank, Budheg Ngeluruk, and Al Fatehahan.